Dynamics of elastin in liver fibrosis: Accumulates late during progression and degrades slowly in regression. Issue 12 (17th May 2019) - Chen, Wei; Yan, Xuzhen; Xu, Anjian; Sun, Yameng; Wang, Bingqiong; Huang, Tao; Wang, Huan; Cong, Min; Wang, Ping; Yang, Aiting; Jia, Jidong; You, Hong
Abstract: Elastin is an amorphous protein highly resistant to elastase degradation and is believed to be the most stable component among the extracellular matrix (ECM) members. Thus the excessive deposition of elastin in advanced liver fibrosis may contribute to the declining reversibility of the disease. Our previous study has found that elastin crosslinking inhibition can effectively arrest liver fibrosis progression. To further understand the roles of elastin involved in liver fibrosis, we systematically investigated the expression, accumulation, and degradation based on dynamic and bidirectional CCl4 ‐induced liver fibrosis mouse models and visualized the ultrastructure of elastin globules in cultured LX‐2 cells. We found that the expression pattern of tropoelastin (soluble elastin) and collagen I was not completely comparable at both the transcriptional and posttranscriptional levels during liver fibrosis progression and regression. Elastin mainly accumulated onto the internodular fibrous septa and enlarged portal areas and intertwined with collagen I at the late stage of liver fibrosis. Three‐dimensional analysis of elastin and collagen I by confocal immunofluorescence coupled with biochemical analyses revealed that with respect to collagen, elastin deposition was characterized by late aggregation in progression and slow turnover in regression. In addition, we visualized the dynamic ultrastructure of ECM fibers during liver fibrogenesis and fibrolysis and the ultrastructure of elastin globules self‐aggregated by tropoelastin crosslinking. Our current study established new general hallmarks of elastin levels and forms in progressive and regressive liver fibrosis and provided a foundation for further experimental investigation of the growing role of elastin in liver fibrosis regression. Abstract : Expression pattern of elastin and collagen I was not completely comparable at both the transcriptional and posttranscriptional levels during liver fibrosis progression and regression. Elastin deposition was characterized by late aggregation in progression and slow turnover in regression. Dynamic ultrastructure of the extracellular matrix fibers during liver fibrogenesis and fibrolysis and the ultrastructure of elastin globules self‐aggregated by tropoelastin crosslinking were visualized.